(untitled) (Research, Society and Development, 2020)
Fungi are organisms capable of synthesizing metabolites of industrial interest and the standardization of biomass production for the extraction of these compounds has biotechnological applications. The objective of this work was to optimize the in vitro cultivation process for fungi isolated from Pinus sp., standardizing the best conditions for the production of biomass, contributing to its large scale production. Therefore, the conditions of in vitro cultivation of the fungi Botrytis cinerea, Rhizoctonia sp. and Suillus sp., were evaluated based on the maximum production of dry biomass (PBS), varying temperature, medium and cultivation time. The fungi were grown in glass flasks with liquid culture media, in a BOD chamber, without mechanical stirring. Potato-dextrose broth - PD broth (PD), Czapek - CZ broth (CZ) and Malt Extract - EM broth (EM) were evaluated at temperatures ranging from 8 to 32 ºC and incubation times from 7 to 35 days. PD broth showed better results for fungi B.cinerea and Rhizoctonia sp., when compared to CZ and EM broths, in PBS, while Suillus sp. showed better development in EM broth. The best growth temperature based on PBS was 12 ºC and 16 ºC, with 28 and 35 days of cultivation.